iDS372, a Phenotypically Reconciled Model for the Metabolism of Streptococcus pneumoniae Strain R6 - Dias, Oscar; Saraiva, João; Faria, Cristiana; Ramirez, Mario; Pinto, Francisco; Rocha, Isabel (Frontiers in Microbiology, 2019)
A high-quality GSM model for Streptococcus pneumoniae R6 model strain (iDS372), comprising 372 genes and 529 reactions, was developed. The construction of this model involved performing a genome-wide reannotation to identify the metabolic capacity of the bacterium. A reaction representing the abstraction of the biomass composition was reconciled from several studies reported in the literature and previous models, and included in the model. The final model comprises two compartments and manifold automatically generated gene rules. The validation was performed with experimental data from recent studies, regarding the usability of carbon sources, the effect of the presence of oxygen and the requirement of amino acids for growth. This model can be used to better understand the metabolism of this major pathogen, provide clues regarding new drug targets and eventually design strategies for fighting infections by these bacteria.